Ornamental Plant Growth in Different Culture Conditions and Fluoride and Chloride Removals with Constructed Wetlands - José Luis Marín-Muñiz; María E. Hernández; Sergio Zamora Castro (Hydrology)
Natural water resources often contain fluorides and chlorides due to wastewater discharge; however, excessive exposure to fluorides can pose health risks to humans. Elevated chloride levels can negatively affect aquatic fauna and disrupt the reproductive rates of plants. This study assessed constructed wetlands (CWs) featuring monocultures (including Canna hybrid, Alpinia purpurata, and Hedychium coronarium) and polycultures (combinations of species from the monoculture systems) of ornamental plants (OPs) to evaluate their efficiency in removing fluorides and chlorides. The results revealed that the ornamental plants flourished in the CW conditions without sustaining any physical damage. C. hybrid demonstrated the longest roots and the highest volume, as well as greater height compared to other species. However, this did not affect the ion removal efficiency. In polyculture systems, 42.2 ± 8.8% of fluoride was removed, a result that was not significantly different (p > 0.05) from the removal rates observed in monocultures of C. hybrid (42.5 ± 7.5%), H. coronarium (36.8 ± 7.0%), or A. purpurata (30.7 ± 7.9%). For chloride, a similar pattern emerged, with 32.4 ± 4.8% removed in constructed wetlands (CWs) using a polyculture of ornamental plants, a figure that was also not significantly different (p > 0.05) from the removal percentages in monocultures of C. hybrid (29.1 ± 5.3%), H. coronarium (28.1 ± 5.0%), or A. purpurata (32.0 ± 5.7%). Our results indicate that CWs with polyculture species contribute to pollutant removal at levels comparable to those found in monoculture systems. However, polyculture systems offer enhanced aesthetic appeal and biodiversity, incorporating various ornamental flowering plants. The use of this eco-technology for removing fluoride and chloride pollutants helps prevent river contamination and associated health issues.